Quality control model for biochemical and ultrasound markers in prenatal screening for fetal aneuploidies with laboratory-centralized management - Ramírez Garrido, F; Ulibarrena Estevez, J; Valverde Cuesta, S; Ramayo Barrio, E; Camacho Carretero, A (2012)
Introduction: First trimester combined fetal aneuploidy screening is the most widely implemented model at national level. Although it is well established to perform quality control of biochemical measurements, it has been seldom applied to ultrasound measures.The aim of this paper is to describe how to implement a model of quality control in the laboratory, which includes all markers in prenatal screening for aneuploidy. Methods: We have evaluated the precision and bias of biochemical markers. In the case of nuchal translucency (NT), the WIHRI method was employed to control quality, and CUSUM was applied to each ultrasound operator with the values extracted from the computer software database. Results: For the biochemical parameters CV was below 4%. The bias was within the specification for the analyte concentration levels, as was the case for MoMs, except for one month. Quality control of NT showed that 5 of the 8 ultrasound operators evaluated sdid not comply with the quality criteria when using the WIHRI method, and 6 when CUSUM was applied. Conclusions: After showing the difficulty in obtaining accurate NT measurements to the professionals involved, it was possible to reach a consensus on using the CUSUM method for quality control of NT. In this way, the laboratory will be responsible for sending a report to each ultrasound operatorin the cases where the deviation exceeds the established limit. © 2011 AEBM, AEFA y SEQC.